Studies on Rainfall Characteristics at Kota - Handa, D. P.; Mishra, P. R. (Indian Forester, 1968)
Analytical presentation of 75 years of rainfall data of Kota has been attempted in this paper. Variability of annual rainfall, its trend, annual and monthly distribution together with the maximum intensity of different storms ranging from 5 minutes to 60 minutes duration have been presented. The analysis indicates a slight increasing trend in the annual precipitation. While there is a wide variability in rainfall from year to year and from month to month, the study reveals a better consistency in the distribution of rainfall during Kharif season, while during Rabi season the variability in distribution is much more. There appears to be no hope for increasing production without adequate measures for conserving water and without providing irrigation facilities in the region.